2018
DOI: 10.1093/jas/sky022
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-specific responses reveal an important role of lipogenesis during heat stress adaptation in pigs1

Abstract: Elevated ambient temperature causes heat stress in pigs, resulting in reduced animal performance. To better understand tissue responses to heat stress in pigs, we conducted a study in which pigs were subjected to four treatments: acute (24 h) heat stress (AHS) at 35 °C ± 1 ambient temperature, chronic (7 d) heat stress at 35 °C ± 1 (HS) or normal ambient temperature (20 °C± 1) for 7 d with ad-libitum feeding (Con) or with pair-feeding to the feed intake (FI) of the HS pigs (PF). Heat stress decreased FI by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…6A). It has also been reported that the gender of pigs might affect the HS response [27,28]. In the present study, the glutamate and leucine levels in the saliva samples from the male pigs decreased and the concentrations of glucose and alanine tended to decrease by HS.…”
Section: Discussionsupporting
confidence: 60%
“…6A). It has also been reported that the gender of pigs might affect the HS response [27,28]. In the present study, the glutamate and leucine levels in the saliva samples from the male pigs decreased and the concentrations of glucose and alanine tended to decrease by HS.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, our current study found that HSP70 was increased in both abdominal fat and liver and HSP27 was increased in the liver, indicating the adaptive response of these piglets in response to heat stress even when they were in utero of sows and during lactation period. It has also been reported that heat stress elevated glyceroneogenesis and increased fat storage in pigs (Qu et al 2016;Qu and Ajuwon 2018). Liver and lipid tissue are two major organs regulating lipogenesis in animals.…”
Section: Discussionmentioning
confidence: 97%
“…Altered insulin sensitivity is suggested to be responsible for enhanced lipid deposition. Reduced lipolysis activity in adipose tissue appears to be an adaptive form to limit heat production in heat-stressed animals [8][9][10]. Lipids play an essential role in regulating several biological processes involved in heat stress response [11].…”
Section: Introductionmentioning
confidence: 99%